PROBLEM PENGEMBANGAN KURIKULUM DI LEMBAGA PENDIDIKAN ISLAM - Shohib B; Ifada Retno Ekaningrum; Tedi Kholiludin (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Islamic education plays a vital role in shaping character and morality, yet its curriculum development process often faces significant challenges. The primary focus of this study is to understand the various obstacles encountered in integrating Islamic values with the demands of modern education. The research methodology used is a literature review and qualitative analysis of various curriculum policies and practices in Islamic educational institutions. The findings indicate several key problems, including: the dichotomy between religious and general sciences, which creates a separate and poorly integrated curriculum; the limited competence of teachers in adopting innovative teaching methods; resistance to change from some traditionalist viewpoints; and the lack of curriculum relevance to the needs of the workforce and technological advancements. In conclusion, curriculum development in Islamic educational institutions requires a holistic and comprehensive approach. Necessary efforts include strengthening the capacity of human resources (teachers), restructuring the curriculum to achieve a balanced integration, and adapting to modern developments without sacrificing fundamental Islamic values. This study recommends the need for collaboration among academics, education practitioners, and other stakeholders to formulate a curriculum development model that is relevant, dynamic, and sustainable.